Development of secure web base press release site (TOC, Abstract, Chapter 1 and Reference only) - Eidul Ameen Sahul Hameed (2014)
The purpose of the study is to develop a secure web based press release site. To develop any system the most important part is get the functional requirement right in the first place, because the cost of fixing a wrong functional requirement is much more costly than fixing normal programming error. Unified Modeling Language (UML) use case diagram is used to model the system and entity relationship diagram is used to design the database. Security is very paramount for any web based application that is continuously being threatened with types of security risks. Therefore, the system will be developed by considering the threat of security risk such as SQL injection risk, XSS flaws and cross site request forgery. The system to be hosted at live site and it shall be accessible for anyone to post the press release. (ABSTRACT BY AUTHOR)